Return to Work in Patients with an Ankle Fracture and the Influence of Physiotherapy - Van Vehmendahl, Robyn; P.J. Smeeing, Diederik; Edwards, Michael; Pull ter Gunne, Albert; L. Tiel Groenestege, Dieuwertje; Bemelman, Michael; Nelen, Stijn (Journal of the Foot & Ankle, 2024)
Objective: The role of physiotherapy in the treatment of ankle fractures is unclear. The aim of this study is to assess the influence of physiotherapy on return to work (RTW) in patients with an ankle fracture. Method: A retrospective cohort study was conducted on patients of 18 years and older with a conservatively or surgically treated ankle fracture in one of four regional hospitals in the Netherlands between 2017 and 2019. Patient and treatment characteristics were extracted from medical records. Questionnaires were sent to receive information about RTW. Results: A total of 1804 patients met the inclusion criteria in this study and 1163 patients replied to the questionnaire (64.5%). Two groups were formed: patients who received physiotherapy (n=573) and patients who did not receive physiotherapy (n=582). Patients who had physiotherapy were more often older, female, had more inherently unstable and open fracture types, were more often operatively treated, more often treated using cast immobilization, experienced complications more often and needed revision surgery more often. Physiotherapy was seen to be a significant negative associative factor for RTW (HR = 0.768). Conclusion: Overall, 5% of all patients sustaining an ankle fracture did not RTW. Although in part explained by fracture-, treatment- and patient characteristics physiotherapy tends to negatively affect time to RTW in patients with an ankle fracture. Level of Evidence II prognostic study, retrospective study